Search for sneutrino production in eμ final states in 5.3fb-1 of pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (American Physical Society (APS), 2010)
We report the results of a search for R parity violating (RPV) interactions leading to the production of supersymmetric sneutrinos decaying into eμ final states using 5.3fb⊃-1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider. Having observed no evidence for production of eμ resonances, we set direct bounds on the RPV couplings λ311′ and λ312 as a function of sneutrino mass. © 2010 The American Physical Society.